Implementación de un sistema de control interno de inventarios y la rentabilidad de la Fábrica de Calzado “LOGATTY” de la ciudad de Ambato en el período 2022 - Pilamunga Jindi, Jenny Del Rocío (2022)
The objective of this research was to design an internal inventory control system and its impact on the profitability of the “LOGATTY” footwear factory in the city of Ambato in the period 2022, for which a methodology was established under a quantitative approach, of type descriptive, correlational, bibliographic and field, for which it was necessary to use the application of surveys as a data collection technique using structured questionnaires as an instrument. The results revealed that the company lacks adequate internal inventory control, in that sense, through the Chi square analysis it was possible to verify that the inventory control activities do have a significant impact on the organization's profitability. Finally, it is concluded that the "LOGATTY" footwear factory does not have adequate internal inventory control that allows it to improve its profitability, this shows that the company does not have an inventory control policy and procedures, for Therefore, the implementation of an internal inventory control system based on the COSO III model for the "LOGATTY" shoe factory is recommended, which will allow improving internal control and this in turn will increase the profitability of the company.